Governing in a polarized age elections, parties and political representation in america - Gerber, Alan S.; Schickler, Eric 1969- (Cambridge University Press, 2017)
"Many political observers have expressed doubts as to whether America's leaders are up to the task of addressing major policy challenges. Yet much of the critical commentary lacks grounding in the systematic analysis of the core institutions of the American political system including elections, representation, and the law-making process. Governing in a Polarized Age brings together more than a dozen leading scholars to provide an in-depth examination of representation and legislative performance. Drawing upon the seminal work of David Mayhew as a point of departure, these essays explore the dynamics of incumbency advantage in today's polarized Congress, asking whether the focus on individual re-election that was the hallmark of Mayhew's ground-breaking book, Congress: The Electoral Connection, remains useful for understanding today's Congress. The essays link the study of elections with close analysis of changes in party organization and with a series of systematic assessments of the quality of legislative performance"...
Includes bibliographical references and index
Keywords: United States -- Congress -- Elections; Incumbency (Public officers) -- United States; Representative government and representation -- United States; Polarization (Social sciences) -- United States; Polarisierung; Parlamentswahl; Repräsentation -- Politik; USA; Aufsatzsammlung